2019
DOI: 10.3390/polym11122065
|View full text |Cite
|
Sign up to set email alerts
|

Development and Properties of Fish Gelatin/Oxidized Starch Double Network Film Catalyzed by Thermal Treatment and Schiff’ Base Reaction

Abstract: In order to improve the properties of fish gelatin (FG), oxidized starch (OS) was adopted to form hetero-covalent linkage with it based on thermal treatment and the Schiff' base reaction. The effects of different ratios of FG/OS (ranging from 10:1 to 2:1) on the properties of films were investigated. OS improved the mechanical and barrier properties of films significantly, while the moisture content decreased as OS concentration increased. The optimum concentration was obtained at the loading amount of 1.5% (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The infrared spectra were recorded in the wavelength range from 500 cm −1 –4000 cm −1 . The characteristic absorption band in the 1047 cm −1 region of the FTIR spectrum was related to the organic components (Si-O-Si) of the MSCS concentration [ 31 ]. With the addition of GR, there was a significant increase in FTIR spectra at the 1047 cm −1 and 1087 cm −1 region [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The infrared spectra were recorded in the wavelength range from 500 cm −1 –4000 cm −1 . The characteristic absorption band in the 1047 cm −1 region of the FTIR spectrum was related to the organic components (Si-O-Si) of the MSCS concentration [ 31 ]. With the addition of GR, there was a significant increase in FTIR spectra at the 1047 cm −1 and 1087 cm −1 region [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, GelMa has been proven to be able to enhance in vitro osteogenic differentiation and calcium deposition as well as enhance in vivo endochondral bone formation [25]. In this study, we will use gelatin sourced from fish collagen provided from the recycling of an unutilized resource and successive high value-added products [26]. Results from our previous studies have shown that mesoporous calcium silicate scaffolds could be loaded with BMP-2.…”
Section: Introductionmentioning
confidence: 99%
“…FTIR was performed to further confirm the presence of CS in the GelMa and to characterize the interactions between the CS and GelMa. As shown in Figure 2B, CS10 had Si-O-Si, Si-O-Ca, and O-Si-O peaks at 1150, 1000, and 650 cm −1 , respectively, whilst CS0 had C-O, N-H, and C-N peaks at 1650, 1550, and 1250 cm −1 , respectively [29]. These results indicated that CS was successfully incorporated into the GelMa via a covalent bond and that different concentrations of CS were also successfully loaded, as seen from the difference in intensity in both CS5 and CS10.…”
Section: Synthesis and Characterization Of The Cs/gelma Scaffoldmentioning
confidence: 95%